The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1016/j.optmat.2005.09.055
|View full text |Cite
|
Sign up to set email alerts
|

Photon management with lanthanides

Abstract: Efficient conversion of photons from high energy radiation (e.g. ultraviolet or X-rays) to lower energies (visible) has been optimized by using luminescent materials based on the optical properties of lanthanide ions. Presently, luminescent materials with efficiencies close to the theoretical maximum are applied in e.g. fluorescent tubes, X-ray imaging and color television. Contrary to the mature status of luminescent materials in these fields, areas requiring new luminescent materials are emerging. There is g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 15 publications
1
29
0
2
Order By: Relevance
“…Nie et al [16], on the other hand, reported the energy transfer between Pr 3+ and Cr 3+ in SrAl 12 O 19 . Vergeer et al [17] and Meijerink et al [18] found it difficult to find the efficient energy transfer from Pr 3+ to Eu 3+ irrespective of the fulfilment of an important condition for energy transfer which is the presence of resonance between Pr 3+ and Eu 3+ ions. The luminescence intensities were compared for different gels with and without Mg particles by varying the different concentrations of Mg [19].…”
Section: Resultsmentioning
confidence: 99%
“…Nie et al [16], on the other hand, reported the energy transfer between Pr 3+ and Cr 3+ in SrAl 12 O 19 . Vergeer et al [17] and Meijerink et al [18] found it difficult to find the efficient energy transfer from Pr 3+ to Eu 3+ irrespective of the fulfilment of an important condition for energy transfer which is the presence of resonance between Pr 3+ and Eu 3+ ions. The luminescence intensities were compared for different gels with and without Mg particles by varying the different concentrations of Mg [19].…”
Section: Resultsmentioning
confidence: 99%
“…-Mn 2? dual doped KMgF 3 [39], SrY 2 F 8 , YF 3 [40], SrBO 3 [41]. The visible emission spectra of dual doped phosphor shown in Fig.…”
Section: Fluorescence Concentration Quenchingmentioning
confidence: 98%
“…and Mn 2? ions, no efficient energy transfer process occurs between them in Ca 0.5 La(MoO 4 ) 2 might be attributed to the selection rules, cross relaxation process, nearest neighboring pairs, total spin of the system change [9,[38][39][40]. By analyzing reflectance and excitation spectra it is recognized that the expected spectral overlaps between Pr 3?…”
Section: Fluorescence Concentration Quenchingmentioning
confidence: 99%
“…The 3 P 2 , 1 I 0 and P 0 levels at between 440 and 490 nm can absorb blue photons that can then radiatively recombine via the 1 G 4 level at 1010 nm -at just greater than twice this wavelength -thus emitting two photons at just above the silicon bandgap, although nonradiative recombination via the other levels at longer wavelengths than 1 G 4 is also likely. Experiments indicating such photon cutting have been carried out on Pr 3 + embedded in various phosphors, [Meijerink et al, 2006], and also for other lanthanide-doped materials, [Wegh et al, 2002, Michels et al, 2002. Transition metals with their partially screened 'd' shell electrons also have partially discrete levels and work on photon cutting in transition-metal-doped materials has also been carried out, [Ilmas, 1970, Berkowitz andOlsen, 1991].…”
Section: Lanthanide-based DCmentioning
confidence: 99%